Determinasi Return on Asset, Net Profit Margin, dan Total Asset Turnover terhadap Pertumbuhan Laba pada Perusahaan Sektor Pertambangan di Bursa Efek Indonesia - Rahmatia (Jurnal Ekonomi Islam, 2022)
This study aims is to generate the concept of the magnitude of the effect of return on assets, net profit margin and total asset turnover on profit growth and which variables are dominant influence on profit growth in mining sector companies listed on the stock exchange Indonesia. This study uses quantitative methods with the analysis tool used is multiple regression. The population in this study are all mining sector companies listed on the Indonesia Stock Exchange as many as 39 companies and the sample method used is purposive sampling method with criteria that is mining sector companies listed on the Indonesia Stock Exchange, have financial reports for the last five years. The results of this study meyebutkan Return on asset and total assets turnover proved empirically has a significant contribution to profit growth, Net Profit Margin has no effect on profit growth in mining companies listed on the BEI period 2016-2021.